Benthic Observation Survey System (BOSS) for surveys of marine benthic habitats - Tim Langlois; Claude Spencer; Brooke A. Gibbons; Kingsley J. Griffin; Kye Adams; Charlotte Aston; Neville Barrett; Ashlee Bastiaansen; Donna Beach; Ant Bernard; Todd Bond; Genevieve R. Carey; et al. (Methods in Ecology and Evolution)
Abstract Most platforms for collecting images to characterise marine benthic habitats involve a downward or forward‐facing field of view that is relatively constrained (~70°), covering a relatively small area of benthos (downward ~1 m2, forward ~25 m2). Here we propose the use of a four‐camera platform having a wide combined field of view (~280°), covering a much greater area (up to 100 m2). We also present a stereo‐camera configuration that has the added benefit of being able to accurately measure sample area and dimensions of benthic biota. The design proposed is robust and self‐righting, facilitating rapid deployment and retrieval from a range of vessels, depths and environments. We present an exemplar workflow to generate a habitat map (~100 km2) within a no‐take National Park Zone within the South‐west Corner Marine Park, Australia and demonstrate the benefit of increasing the field of view to estimate habitat heterogeneity. The relatively broad sample unit of this wide‐field drop camera is well suited to estimating coverage (e.g. of a seagrass bed) and habitat mapping. It is time‐efficient in the field, enabling spatially balanced sampling designs to acquire ground‐truthing data for medium‐ to large‐scale habitat mapping projects. This platform is a practical tool to monitor change in marine environments and assess the environmental impact (e.g. sea bed alteration) of activities such as offshore energy or fishing gears.